Labour supply and taxes: New estimates of the responses of wives to husbands' wages - Benoit Dostie; Lene Kromann (Institute for the Study of Labor (IZA), 2012)
In this paper, we estimate income- and substitution- labour supply and participation elasticities for Canadian married women using data from the Survey of Labour and Income Dynamics 1996-2005. We use the Canadian Tax and Credit Simulator (CTaCS) and detailed information on the structure of income at the household level to compute the marginal tax rates faced by each individual. We then use these marginal tax rates to compute net own-wage, spouse-wage, and non-labour income. We show how the magnitude of the estimated elasticities varies depending on whether net or gross wages and income are used in the estimation procedure, and quantify biases caused by using average instead of marginal tax rates. Finally, because marginal tax rates vary significantly over the sample, we use quantile regressions to compare elasticities at different points of the hours distribution. Overall, our results show that public policies now have, on average, less scope for influencing hours of work than 10 years ago. However, the quantile results show that wives working fewer hours per week are more sensitive to changes in their own or spouses' wages.
urn:nbn:de:101:1-201206146688
Keywords: C25; H31; J22; 330; labour supply; elasticities; labour force participation; taxes; Canada; Weibliche Arbeitskräfte; Ehe; Arbeitsangebot; Steuer; Lohn; Elastizität; Schätzung; Kanada